Language and Organization - Daft, Richard L.; Wiginton, John C. (Academy of Management Review, 1979)
This paper argues that insight into organization functioning is related to the fit between language of description and type of organizational phenomenon. Natural language may be more powerful than mathematical language for understanding and describing many organization processes.